The Atypical Cadherin FAT1 Limits Mitochondrial Respiration and Proliferation of Vascular Smooth Muscle Cells - Riascos-Bernal, Dario F.; Maira, Alishba; Sibinga, Nicholas E. S. (Frontiers in Cardiovascular Medicine, 2022)
Smooth muscle cells contribute to cardiovascular disease, the leading cause of death worldwide. The capacity of these cells to undergo phenotypic switching in mature arteries of the systemic circulation underlies their pathogenic role in atherosclerosis and restenosis, among other vascular diseases. Growth factors and cytokines, extracellular matrix components, regulation of gene expression, neuronal influences, and mechanical forces contribute to smooth muscle cell phenotypic switching. Comparatively little is known about cell metabolism in this process. Studies of cancer and endothelial cell biology have highlighted the importance of cellular metabolic processes for phenotypic transitions that accompany tumor growth and angiogenesis. However, the understanding of cell metabolism during smooth muscle cell phenotypic modulation is incipient. Studies of the atypical cadherin FAT1, which is strongly upregulated in smooth muscle cells in response to arterial injury, suggest that it has important and distinctive functions in this context, mediating control of both smooth muscle cell mitochondrial metabolism and cell proliferation. Here we review the progress made in understanding how FAT1 affects the smooth muscle cell phenotype, highlighting the significance of FAT1 as a processed protein and unexpected regulator of mitochondrial respiration. These mechanisms suggest how a transmembrane protein may relay signals from the extracellular milieu to mitochondria to control metabolic activity during smooth muscle cell phenotypic switching.